Influence of non-steroidal anti-inflammatory drugs on the outcome of faecal occult blood tests in screening for colorectal cancer. - Pye, G (1987)
Non-steroidal anti-inflammatory drugs have been accused of causing false positive results in faecal occult blood tests for colorectal cancer. A study was therefore performed in 10,931 people undergoing faecal occult blood screening tests to assess the effect of these drugs on the predictive value of a positive test result. Those with a positive result were interviewed and a full drug history was taken before they underwent a full colorectal examination. Of the 455 people with a positive result, 50 were taking non-steroidal anti-inflammatory drugs: 10 (20%) had colonic neoplasia. Of the 405 who were not taking non-steroidal anti-inflammatory drugs, 129 (32%) had colonic neoplasia. These detection rates were not significantly different, and the predictive value of a positive result for an adenoma larger than 1 cm was 14% in the group not taking anti-inflammatory drugs and 26% in the group taking them (not significant). These results suggest that a finding of occult faecal blood cannot be attributed to upper gastrointestinal tract bleeding caused by non-steroidal anti-inflammatory drugs and should be followed by a thorough colorectal examination.